Shape transitions of epitaxial islands during strained layer growth: anatase TiO2(001) on SrTiO3(001). - Marshall, MS; Castell, M (2009)
Extended annealing in UHV causes the surface region of SrTiO3(001) to become enriched with TiO2, resulting in the formation of epitaxial islands of anatase TiO2(001). The islands are studied using UHV scanning electron microscopy (SEM), which reveals the changes in morphology during growth induced by misfit strain. Starting from a square island, two types of shape transition are observed. In the first, between 1000 and 1030 degrees C, the anatase islands elongate in length and narrow in width. This growth behavior follows the Tersoff-Tromp model [Phys. Rev. Lett. 70, 2782 (1993)10.1103/PhysRevLett.70.2782]. In the second growth mode, between 930 and 1000 degrees C, the islands relieve strain by the formation of trenches in the middle of each side of the square, thereby evolving into crosses. This shape arises because the lower annealing temperature imposes a kinetic constraint on the detachment of atoms necessary for island narrowing.